Spatio-temporal structure of Cherenkov radiation excited by a laser pulse in an ionic dielectric waveguide - Balakirev, V.A.; Markov, P.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2021)
The process of excitation of Cherenkov electromagnetic radiation by a laser pulse in an ionic dielectric waveguide, is investigated. The frequency spectrum and mode composition of the Cherenkov radiation are determined. The spatio-temporal structure of the Cherenkov electromagnetic field is obtained and investigated. Досліджено процес збудження черенковського електромагнітного випромінювання лазерним імпульсом в іонному діелектричному хвилеводі. Визначено частотний спектр та модовий склад черенковського випромінювання. Отримана й досліджена просторово-часова структура черенковського електромагнітного поля. Исследован процесс возбуждения черенковского электромагнитного излучения лазерным импульсом в ионном диэлектрическом волноводе. Определены частотный спектр и модовый состав черенковского излучения. Полученa и исследована пространственно-временная структура черенковского электромагнитного поля.